SYNTHESIS, SPECTRAL CHARACTERIZATION OF BIOLOGICALLY ACTIVE NOVEL SCHIFF BASE COMPLEXES DERIVED FROM 2-SULPHANILAMIDOPYRIMIDINE - G.VALARMATHY; R.SUBBALAKSHMI (International Journal of Pharma and Bio Sciences, 2013)
New Schiff base has been prepared from 2-sulphanilamidopyrimidine and 2-hydroxy-3-methoxy benzaldehyde in ethanolic media and then complexed with Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) ions. The synthesized ligand and complexes were characterised by Elemental analysis, Molar conductance,Magnetic susceptibility,IR, UV,1H & 13C NMR, , EPR, and. The Spectral data confirms well coordination of Schiff-base ligand with the metal through imine nitrogen and oxygen atoms of Schiff base moiety. The Schiff base ligand and the complexes were screened for antimicrobial activity and fluorescent behaviour. From the analytical and spectral data, the stoichiometry has been found to be 1:2 for all the complexes. An octahedral structure has been proposed. All the new complexes were found to be active against bacteria and fungi.